الأفعال المتعدّية بحرف الجرّ في كتاب القراءة الوافية المقرّر للصّفّ السّادس دلالية / Transgressive verbs (Harf Jar) in the sixth-grade reading book (Grammatica / Transgressive verbs (Harf Jar) in the sixth-grade reading book (Grammatical semantic study) - Said, Abdul Hafidz; Fitrianto, Ibnu; Jamilah , Hasna Awwaliyah (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
والهدف من هذا البحث هو الكشف عن حروف الجرّ التي يتعدّى بها الفعل في كتاب القراءة الوافية المقرّر للصّفّ السّادس والكشف عن معاني الأفعال المتعدّية بحروف الجرّ فيه، ولتحقيق الهدف المرجوّ استخدم الباحثون المنهج المكتبيّ حيث قاموا بمطالعة الكتب مما يتعلّق بالأفعال المتعدّية. ولتحليل المسألة البحثية انتهجوا المنهج الوصفيّ التّحليليّ وتحليل المحتوى للحصول على النتائج الوثيقة. أمّا نتيجة البحث فهي: أنّ حروف الجرّ التي يتعدّى بها الفعل في الكتاب المذكور فهي: "على" وتتمثل في 28 جملة و"عن" وتتمثل في 12 جملة وحرف "من" وتتمثل في جملة واحدة، و"إلى" وتتمثل في 9 جمل، و"في" وتتمثل في 7 جمل والباء وتتمثل في 25 جملة و" اللام" وتتمثل في 10 جمل، إذ تقع هذه ألافعال المتعدّية بـ "في" في 92 جملة مشتملة على 58 فعلا. و قد اختلفت معاني الأفعال بسبب اختلاف حروف الجرّ التي تتعدّى بها، فتسمّى الأفعال المتعدّية بحرف الجرّ، وقد ثبتت معاني الأفعال المتعدّية بحرف الجرّ وتبقى معانيها. الكلمة المفتاحية : الأفعال؛ المتعدّية؛ حروف الجرّ؛ القراءة الوافية Abstract The goals of this study are to discover the prepositions through which the verb transcends in the comprehensive reading book for class six, as well as the meanings of transitive verbs with prepositions in the comprehensive reading book for class six. To achieve the desired results, the researcher used the literature method, which entailed reading books about transitive verbs. The researcher adopted the descriptive-analytical approach and analyzed the content to obtain the documented results. As for the result of the research, it is that the prepositions that transcend the verb in the adequate reading book for the sixth grade are Harf ̔ala on in 28 sentences and Harf an in 12 sentences, and Harf min in one sentence, Harf il in 9 sentences, Harf fī in 7 sentences, Harf ba̕ in 25 sentences, and Harf lam in 10 sentences. These transitive verbs with a preposition are found in 92 sentences, in which 58 verbs are included. The meanings of the verbs have differed because of the different prepositions that transitive verbs have, so transitive verbs are called prepositions. The meanings of transitive verbs with a preposition have been established, and their meanings remain.